Developing a vocational engineering word list: Bridging the gaps of secondary and tertiary education - Jin N.Y.; Tong C.S.; Shyuan L.K.; Abd Rahman A.Z.; Thiruchelvam S. (Mattingley Publishing, 2023)
Bridges; Content analysis; Corpus linguistics; Creation process; Engineering words; English word lists; Pedagogic engineerings; Technical engineering; Tertiary education; Engineering education